2016
DOI: 10.1039/c5cy01992c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanofiber-supported ReOx catalysts for the hydrodeoxygenation of lignin-derived compounds

Abstract: The effect of ReOx loading (2–13 wt%) and H2 pressure (0–5 MPa) for the hydrodeoxygenation of phenol has been studied for carbon nanofiber-supported ReOx catalysts in a batch reactor at 573 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 74 publications
3
52
0
Order By: Relevance
“…Reactivity of anisole higher than guaiacol reported in [39] similarly to the work of Prasomsri et al [36], can be explained by a higher bond dissociation energy required for the aromatic hydroxyl compared to methoxyl (Table 3). For o-cresol the preferred route is demethoxylation followed by ring hydrogenation [37]. Only when HDO was performed at 400 °C over Pt-Sn/CNF/Inconel nickel-(Inconel is chromium-based superalloy), guaiacol reactivity was higher than for anisole probably due to a very high temperature [48].…”
Section: Comparative Studies Of a Single Feed Reactant Over The Same mentioning
confidence: 99%
See 3 more Smart Citations
“…Reactivity of anisole higher than guaiacol reported in [39] similarly to the work of Prasomsri et al [36], can be explained by a higher bond dissociation energy required for the aromatic hydroxyl compared to methoxyl (Table 3). For o-cresol the preferred route is demethoxylation followed by ring hydrogenation [37]. Only when HDO was performed at 400 °C over Pt-Sn/CNF/Inconel nickel-(Inconel is chromium-based superalloy), guaiacol reactivity was higher than for anisole probably due to a very high temperature [48].…”
Section: Comparative Studies Of a Single Feed Reactant Over The Same mentioning
confidence: 99%
“…It was also observed that when the other hydroxyl was in the meta position, degree of HDO was much higher (Table 1, entry 7). The products in the HDO of guaiacol, phenol and anisole are mainly aromatic compounds, such as benzene and toluene at high temperatures, whereas cyclohexane can be formed below 340 °C over catalysts exhibiting hydrogenation activity, such as supported Ni, Rh, ReOx, CoNx and MoO3 [36,37,43,62,63].…”
Section: Bond Monolignolmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that large BET surface area and acidity of supports were conducive to improving the catalytic efficiency. Ghampson et al investigated ReO x supported on oxidized carbon nanofiber (ReO x -CNFox) to catalyze phenol HDO at 573 K, finding that phenol was completely converted at 10% ReO x loading [99]. The coordinatively unsaturated Re 4+ , which acts as a Lewis acid, interacts with the oxygen lone pair on phenol.…”
Section: Non-noble Metal Catalystsmentioning
confidence: 99%